THE INFLUENCE OF ISLAMIC FINANCIAL BEHAVIOR AND LEARNING MOTIVATION ON THE SUCCESS OF THE KIP KULIAH PROGRAM IN ACHIEVING SDG 4: EVIDENCE FROM THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Lisna Berutu; Marliyah; Nur Ahmadi Bi Rahmani; Mariam Batubara (Ekonomi Islam, 2026)
Research aims: This study examines the impact of Islamic financial behavior and learning motivation on the success of the Kartu Indonesia Pintar (KIP) Kuliah program among recipients at the State Islamic University of North Sumatra, and assesses its implications for advancing the Sustainable Development Goals (SDGs) in education. Design/Methodology/Approach: The research applies a quantitative design using a survey of 96 respondents selected from a population of 2,400 KIP Kuliah participants, as calculated by the Slovin algorithm. The data were analyzed using multiple linear regression analysis. Research findings: The results show that Islamic financial behavior has a positive effect (β = 0.371; Sig. = 0.000), while learning motivation has a stronger positive effect (β = 0.611; Sig. = 0.000) on KIP Kuliah program effectiveness. Together, both variables explain 95.0% of the variation in program effectiveness (R² = 0.950). Theoretical Contribution/Originality: This study offers a novel perspective by integrating Islamic financial behavior and learning motivation into the evaluation of educational program effectiveness, especially social assistance programs aligned with SDGs, with emphasis on SDG 4 concerning inclusive and quality education. Practitioners/Policy Implications: The findings highlight the need for policymakers and educational institutions to strengthen Islamic financial literacy and foster learning motivation to improve KIP Kuliah effectiveness as an investment. Research Limitations/Implications: This study is limited to one university with a modest sample size, which may affect generalizability. Future research should involve samples and additional variables for comprehensive findings.